THE PHENOMENON OF THE UNCANNY AS AN INVERSION OF THE RENAISSANCE IDEAL OF THE BODY - Tahlina, Yuliia; Markhaichuk, Nataliia (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 2025)
The article examines the phenomenon of the uncanny as an inversion of the Renaissance ideal of the body, tracing the transformation of cultural representations of the human body from the Renaissance to the twenty-first century. The article emphasizes that the Renaissance paradigm regarded the body as a symbol of harmony, proportion, and divine perfection, combining physical beauty with spiritual order. In contemporary art, particularly in the body-horror genre, the body emerges as a space of instability, fragmentation, and existential threat, where deformation, anomaly, and the destruction of integrity become key aesthetic and philosophical categories. The author employs historical-cultural, comparative, and phenomenological approaches to analyze the dynamics of changing perceptions of the body. Central to the theoretical understanding of the uncanny are Freud’s concept of the Unheimlich and Kristeva’s concept of the abject, which illuminate the psychological, socio-cultural, and bodily mechanisms of fear, disgust, and the violation of the boundaries of the self. An analytical model of bodily transformation is proposed, structured around three stages: destabilization of form, fragmentation and anomaly, and existential ruination, demonstrating the transition from the harmonious Renaissance body to its contemporary inversion. It is shown that the uncanny does not negate the Renaissance ideal but functions as its mirror image, opening new perspectives for the philosophical, cultural, and aesthetic interpretation of the human body. The inversion of bodily representation in contemporary art reflects a shift in cultural paradigms: the body ceases to be a symbol of order and becomes a space of material and existential vulnerability.